IBU RUMAH TANGGA PENJUAL KORAN DI KOTA PEKANBARU - Sukama Hatika Ria; M. Razif " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This thesis is submitted in order to qualify holds a Bachelor of Sociology. With th e title“Housewives The NewsstanInd Pekanbaru City”. Problem that discuss in the thesis is describing thecharacteristics of the mother the newspaper vendor in terms of the social and economic factors areaffecting the mother worked as a newspaper vendor of the functions of his family as a wife and housewife. Entry of the women in the pulicb sector that aims to help meets the needs of families and theimpact in a floating on the function of his fam ily.The subject of this research amounting to 7 people, and that is locations of them in the SKA, ared light Sudirman and expextations of thhieg hway, a red light of hope highways and kapling, thestop light intersections of arifin ahmad, a red light hit the police, and near Gramedia Library. Thesampling used in this study is a techniquie accidental sampling. The method used method ofqualitative. The theory used to this issue is the theory of structure back whether you thinkfunctionalism is used Talcot Parsons, this theory explains that every thing which when integrated in agroup then the proficiency level has functions, as well as femalesp naepwer vendor. Poverty makeswomen require have a dual role is to play a role in matters of domestic and the public.The results in general, the writer can say that most women who worked as the newspapervendor at the junction of the red light is those wahreo low, which is a eelmentary school and middleschool. The execution of the economic functions for the mother’s family newspaper vendor inpekanbaru city be emplemented by the mother because she wanted to help the family economic. Thefunction of the economic is to meet the needs of families is usually done by the husband but if herhusband has nothing but a mother who is going to carry out economic functions. The functions ofaffection in the mother’s family newspaper vendor carried out in shifts between a mother, childrenand husbands in accordance with the conditions. The functions of sosialization in the familynewspaper vendor was carried out by wives and husbands in accordance with the portions. Aseducating the child is done by tur ns.Keyword: The newspaper vendor, Informal sector